Nutritive quality of eggs from hens fed diets enriched with omega 3 and 9 fatty acids (Semiárida, 2024)
An increasingly representative sector of the society is claiming for egg production systems in line with animal welfare requirements. The production of organic eggs in floor systems is an important alternative. Their added value is constituted by the supply of diets enriched with omega n-3 polyunsaturated fatty acids (n3 PUFA) and omega n-9 monounsaturated fatty acids (n9 MUFA), which greatly benefits human health. Many researchers has a permanent interest in finding ingredients to enrich easy-to-consume and low-cost foods, such as chicken eggs, with n3 PUFA. The present work was done to test possible nutritional quality improvements, in terms of the composition of fatty acids, of eggs laid by hens of the genotype Hy Line Brown in a floor-based production system, when given a diet enriched in PUFA n3 and MUFA n9 by inclusion of ingredients such as soybean expeller, seeds of rape and flax, and fish oil, in comparison with a control traditional diet containing corn and soybean grains. A proximal chromatographic analysis was performed to determine the lipid profile, and the yolk color was assessed based on the international Dutch State Mines Munsell scale (DSM). No significant differences were found between the control and treatment, but adequate relationships PUFA n6/n3 and PUFAIn6/MUFA n9 were observed in those hens given the enriched diet.
Keywords: egg production; rape and flax seeds; fish oil; nutritional value